Analysis of the Pulpal Blood Flow Microdynamics during Prosthetic Tooth Preparation Using Diamond Burs with Different Degrees of Wear - Edmond Ciora; Mariana Miron; Diana Lungeanu; Andreea Igna; Anca Jivanescu (MDPI AG, 2024)
Pulpal modifications taking place during prosthetic tooth preparation using worn-out burs may represent a risk for the vitality of the dental pulp. The aim of this in vivo study was to evaluate whether the wear of diamond burs has an influence on the vascular microdynamics at the level of the dental pulp, during vertical preparation for zirconia crowns. The study was performed with a split-mouth design and included 32 vital permanent monoradicular teeth (20 maxillary and 12 mandibular), from six subjects, aged between 20 and 50 years. The teeth were randomly assigned to two study groups of 16 teeth each. For prosthetic preparation, new burs were used in the first group, and burs at their 5th use were used in the second group. Four consecutive determinations of the pulpal blood flow by Laser Doppler flowmetry (LDF-laser Doppler MoorLab instrument VMS-LDF2, Moor Instruments Ltd., Axminster, UK) were taken for each tooth included in the study: before the preparation (control values), immediately, at 24 h, and at 7 days after the prosthetic preparation. A four-way ANOVA statistical analysis was applied to analyze the effect of four considered factors (bur wear degree, time of measurement, tooth number, and tooth location) on the pulpal blood flow (PBF). A significant increase in pulpal blood flow compared to the baseline was recorded immediately after preparation (p < 0.01), at 24 h (p < 0.01), and at 7 days (p < 0.05) in both groups, but more pronounced in the case of burs at the 5th use. The blood flow was significantly higher in upper jaw teeth, irrespective of the measurement time. In conclusion, the use of worn-out diamond burs produces lasting modifications in the pulpal blood flow of teeth that undergo prosthetic crown preparation. ISRCTN registry: ISRCTN49594720.